Szeged szabad királyi város képviselete az 1843/44. évi országgyűlésen - követutasítások és követjelentések a diétáról - Deák Ádám (Móra Akadémia, 2022)
In my essay, I examine the case of the free royal city through the example of Szeged. I examine based on the speeches of the ambassadors, the instructions of the ambassadors and the reports of the ambassadors. The ambassadorial instructions basically defined the functioning of the national assembly, as the ambassadors had to stick to their instructions, they could not deviate from it, if they did, they could call them back and send someone else in their place. As parliamentary deliberations progressed, more and more cases could arise, in which case the ambassadors do not free to decide for themselves, but had to wait for a replacement order from their municipality. Deciding the case of cities of the cities was important, as all the free royal cities had only one vote. Szeged was represented in this national assembly by Ferdinánd Aigner and Antal Szilber.